Impaired B‐cell tolerance checkpoints promote the development of autoimmune diseases and pathogenic autoantibodies. Issue 1 (12th November 2019) - Meffre, Eric; O'Connor, Kevin C.
Abstract: A role for B cells in autoimmune diseases is now clearly established both in mouse models and humans by successful treatment of multiple sclerosis and rheumatoid arthritis with anti‐CD20 monoclonal antibodies that eliminate B cells. However, the underlying mechanisms by which B cells promote the development of autoimmune diseases remain poorly understood. Here, we review evidence that patients with autoimmune disease suffer from defects in early B‐cell tolerance checkpoints and therefore fail to counterselect developing autoreactive B cells. These B‐cell tolerance defects are primary to autoimmune diseases and may result from altered B‐cell receptor signaling and dysregulated T‐cell/regulatory T‐cell compartment. As a consequence, large numbers of autoreactive naive B cells accumulate in the blood of patients with autoimmune diseases and may promote autoimmunity through the presentation of self‐antigen to T cells. In addition, new evidence suggests that this reservoir of autoreactive naive B cells contains clones that may develop into CD27 − CD21 −/lo B cells associated with increased disease severity and plasma cells secreting potentially pathogenic autoantibodies after the acquisition of somatic hypermutations that improve affinity for self‐antigens.